Prevalence of Helicobacter pylori infection in sexual partners of H. pylori‐infected subjects: Role of gastroesophageal reflux. Issue 10 (1st December 2018) - Sgambato, Dolores; Visciola, Giulio; Ferrante, Emanuele; Miranda, Agnese; Romano, Lorenzo; Tuccillo, Concetta; Manguso, Francesco; Romano, Marco
Abstract : Background: Helicobacter pylori is transmitted through faecal‐oral or oral‐oral routes. Whether H. pylori infection is more prevalent in sexual partners of H. pylori ‐infected subjects is unclear. Objective: We evaluated 1) the prevalence of H. pylori infection in sexual partners of H. pylori‐ infected subjects; and 2) whether presence of gastroesophageal reflux in H. pylori ‐infected subjects was associated with transmission of infection to their sexual partners. Methods: We evaluated H. pylori infection by 13C Urea Breath Test in sexual partners of 161 consecutive patients with H. pylori ‐related dyspepsia. The case‐control group consisted of 161 dyspeptic subjects undergoing the 13C Urea Breath Test. The prevalence of reflux symptoms was noted through the Leeds scale. The role of gastroesophageal reflux in transmission of H. pylori infection was evaluated by binary logistic regression. A two‐tailed p value of 0.05 or less was considered significant. Results: Prevalence of H. pylori infection in sexual partners of H. pylori‐ infected subjects is 74.5% whereas prevalence of H. pylori infection in the control group is 32.3%, p <0.05. At the logistic regression analysis, the presence of reflux symptoms in H. pylori ‐infected subjects is independently associated with concomitant infection in both members of the couple (odds ratio 4.41, 95% confidence interval 1.6–12.3) and with length of cohabitation (odds ratio 2.39, 95% confidence interval 1.0–5.7). Conclusions: The prevalence of H. pylori infection is significantly higher in sexual partners of H. pylori ‐infected subjects than in controls. Members of a couple are four times more likely to be both H. pylori infected if one of the couple has reflux symptoms.